Identifying multiple pollutant catchment risks for the selection and targeting of water industry catchment management interventions: Development, implementation and testing of the CaRPoW framework - Bloodworth, Jack (Cranfield University, 2015)
Water companies are continually adopting catchment management as a way of improving the quality of raw water prior to treatment. The catchments from which raw water is abstracted are often heterogeneous which regularly presents multiple pollutant issues and variability in the spatial distribution of pollutant-contributing areas. For catchment management to be effective, it is crucial that water companies select and target appropriate interventions at multi-pollutant high risk areas. Within this thesis a conceptual framework is developed to disaggregate and compare multiple pollutant risks in drinking water catchments to aid water companies in this decision making process. A review of pollutant processes highlights links between pollutants often mitigated using catchment management and therefore confirms the feasibility for a multi- pollutant framework. Criteria were developed with water industry catchment management professionals to determine framework requirements. No current framework or model fully meets these criteria. ...[cont.]
Keywords: Catchment Management; Water Industry; Diffuse Pollution; Model; Drinking Water